REKAYASA VEGETASI UNTUK KONSERVASI LAHAN RAWAN LONGSOR DI LEMBAH SUNGAI CENGKEHAN, KECAMATAN IMOGIRI, KABUPATEN BANTUL - Rakhman, Arie Noor; -, Muchlis; Septyawan, Bayu Ade (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2020)
This study aims to select vegetation as a landslide controller in the Cengkehan River Valley, Imogiri District, Bantul Regency, Special Region of Yogyakarta. It is adjusted to the characteristics and thickness of the landslide, the height, and slope of the morphology, the typical roots and the suitability of the community interest of the plant species. The slope of the valley is 15°-60° and 75-325 meters above sea level. Landslides are on the north cliff in the direction of landslides, N 234°E, along the morphological orientation directed at N324°E. Landslides are slides that combine with the movement of rocks (wedge failure). Landslide material results from weathering of basalt that the degree of weathering of rock is not continuous between levels III and V. The soil is eluvial sediment which is identified as latosol with thickness up to 2 meters. The recommended vegetation for shallow landslide type is deep-rooted vegetation. They are Dalbergia pinnata and Parkia speciosa, especially for land with slope between 21 to 40%. Recommended vegetation for slopes above 40% is Aleurites moluccana. Latosol conservation for landslide mitigation can be optimized for soil fertility and productivity through the use of straw, leaves and banana peels.